Students' Perception Analysis on the Implementation of Case Method in General Physics and Teaching and Learning Courses - Yudi Pratama; Dios Sarkity (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
This research aims to determine students' perceptions of implementing the case method in general physics and teaching and learning lectures. This research was carried out in July 2023. This research involved 32 first-year students of Biology Education, FKIP UMRAH as research subjects. This research is descriptive research with a quantitative approach. Data was collected through questionnaires to measure student perceptions, including ease, mastery of material, satisfaction, lecturer performance, motivation and activeness. Data were analyzed descriptively. The research results show that students have a very good perception of implementing the case method in general physics lectures and teaching and learning. The percentage of student perceptions regarding implementing the case method in general physics lectures and teaching and learning is not much different. In the indicators of ease, satisfaction, motivation and activeness, Studying and Learning show a higher percentage of perceptions, while for indicators of material mastery and lecturer performance, general physics shows a higher percentage of perceptions. This shows that implementing lectures using the case method is suitable for stimulating activity and increasing students' understanding of concepts in both subjects, such as general physics, and non-exact subjects, such as teaching and learning.